Placental proteome abnormalities in women with gestational diabetes and large-for-gestational-age newborns. Issue 2 (13th November 2020) - Assi, Emma; D'Addio, Francesca; Mandò, Chiara; Maestroni, Anna; Loretelli, Cristian; Ben Nasr, Moufida; Usuelli, Vera; Abdelsalam, Ahmed; Seelam, Andy Joe; Pastore, Ida; Magagnotti, Cinzia; Abdi, Reza; et al.
Abstract : Introduction: Gestational diabetes mellitus (GDM) is the most frequent metabolic complication during pregnancy and is associated with development of short-term and long-term complications for newborns, with large-for-gestational-age (LGA) being particularly common. Interestingly, the mechanism behind altered fetal growth in GDM is only partially understood. Research design and methods: A proteomic approach was used to analyze placental samples obtained from healthy pregnant women (n=5), patients with GDM (n=12) and with GDM and LGA (n=5). Effects of altered proteins on fetal development were tested in vitro in human embryonic stem cells (hESCs). Results: Here, we demonstrate that the placental proteome is altered in pregnant women affected by GDM with LGA, with at least 37 proteins differentially expressed to a higher degree (p<0.05) as compared with those with GDM but without LGA. Among these proteins, 10 are involved in regulating tissue differentiation and/or fetal growth and development, with bone marrow proteoglycan (PRG2) and dipeptidyl peptidase-4 (DPP-4) being highly expressed. Both PRG2 and DPP-4 altered the transcriptome profile of stem cells differentiation markers when tested in vitro in hESCs, suggesting a potential role in the onset of fetal abnormalities. Conclusions: Our findings suggest that placental dysfunction may be directly responsible for abnormal fetal growth/development during GDM. Once established on a larger population, inhibitors of the pathways involving those altered factors may be tested in conditions such as GDM and LGA, in which therapeutic approaches are still lacking.